Current and future challenges of family businesses - Jessica Hastenteufel; Mareike Staub (Managerial Economics)
Family businesses are an important part of every economy. They are characterized by long traditions that combine aspects such as trust and reliability, as well as by features such as innovativeness, foresight, long-term focus and flexibility. Both family businesses and the entrepreneurial families themselves do have some weaknesses and face current challenges like digitization, internationalization and demographic change. These issues must be kept in mind in order to constantly develop appropriate solutions that will help them survive and thrive in the market. Moreover, the high relevance of the family in a family business is associated with opportunities – for example, when a family strategy with clear values, roles and goals is defined, and a so called family business governance is developed.